2011
DOI: 10.1016/j.molcel.2011.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Cardiac PIP3 and cAMP Signaling through a PKA Anchoring Function of p110γ

Abstract: SUMMARY Adrenergic stimulation of the heart engages cAMP and phosphoinositide second messenger signaling cascades. Cardiac phosphoinositide 3-kinase p110γ participates in these processes by sustaining β-adrenergic receptor internalization through its catalytic function and by controlling phosphodiesterase 3B (PDE3B) activity via an unknown kinase-independent mechanism. We have discovered that p110γ anchors protein kinase A (PKA) through a site in its N-terminal region. Anchored PKA activates PDE3B to enhance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
177
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(184 citation statements)
references
References 33 publications
5
177
0
2
Order By: Relevance
“…Thus, the PKA anchoring and sphingosine kinase 1 binding may represent independent aspects of SKIP function that reside within the same polypeptide chain. This concept is reminiscent of how other cardiac PKA anchoring proteins such as AKAPLbc and PI3 kinase γ seem to operate as they also encode catalytic units for guanine nucleotide exchange and lipid kinase activity, respectively (57,58). Alternatively, our MS evidence that SKIP is recruited into higher order macromolecular complexes within the mitochondrial intermembrane space could enhance PKA phosphorylation of ChChd3 (43) and accommodate an antiapoptotic role for sphingosine kinase 1 (53).…”
Section: Discussionmentioning
confidence: 80%
“…Thus, the PKA anchoring and sphingosine kinase 1 binding may represent independent aspects of SKIP function that reside within the same polypeptide chain. This concept is reminiscent of how other cardiac PKA anchoring proteins such as AKAPLbc and PI3 kinase γ seem to operate as they also encode catalytic units for guanine nucleotide exchange and lipid kinase activity, respectively (57,58). Alternatively, our MS evidence that SKIP is recruited into higher order macromolecular complexes within the mitochondrial intermembrane space could enhance PKA phosphorylation of ChChd3 (43) and accommodate an antiapoptotic role for sphingosine kinase 1 (53).…”
Section: Discussionmentioning
confidence: 80%
“…Production of cAMP can be stimulated via ␤-adrenergic pathways or inhibited by PDE3B, which is activated by the insulin-signaling cascade. PKA is activated by cAMP, which can activate PDE3B, creating a negative feedback loop (15,16,19) (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…ezrin (36), sphingosine kinase type 1-interacting protein (61,96), gravin (81), synemin (95), myospryn (92), troponin T (109), and the phosphoinositide 3-kinase p110␥ (90) have been shown to be expressed in cardiac tissues (Table 1). In this context, it is now clear that in the heart, AKAP-based transduction complexes play a crucial role in coordinating signaling pathways that control physiological functions such as Ca 2ϩ cycling, cardiac contractility, and action potential duration, as well as pathophysiological processes including arrhythmias, cardiomyocyte hypertrophy, heart failure, and the adaptive response to hypoxia.…”
Section: Pka Anchoring In the Heartmentioning
confidence: 99%
“…It is now shown that phosphatidylinositol 3-kinase-␥ (PI3K␥) assembles a newly identified signaling complex containing PKA and PDE3B that might regulate ␤-AR expression at the surface of cardiomyocytes (90). In physiological conditions, the ␤-AR/ cAMP pathway leads to the activation of PI3K␥-anchored PKA, which, in turn, phosphorylates PI3K␥ to inhibit its activity (90).…”
Section: Akaps and Heart Failurementioning
confidence: 99%